Metabolomic Analysis of Aspergillus niger Isolated From the International Space Station Reveals Enhanced Production Levels of the Antioxidant Pyranonigrin A - Romsdahl, Jillian; Blachowicz, Adriana; Chiang, Yi-Ming; Venkateswaran, Kasthuri; Wang, Clay C. C. (Frontiers in Microbiology, 2020)
Secondary metabolite (SM) production in Aspergillus niger JSC-093350089, isolated from the International Space Station (ISS), is reported, along with a comparison to the experimentally established strain ATCC 1015. The analysis revealed enhanced production levels of naphtho-γ-pyrones and therapeutically relevant SMs, including bicoumanigrin A, aurasperones A and B, and the antioxidant pyranonigrin A. Genetic variants that may be responsible for increased SM production levels in JSC-093350089 were identified. These findings include INDELs within the predicted promoter region of flbA, which encodes a developmental regulator that modulates pyranonigrin A production via regulation of Fum21. The pyranonigrin A biosynthetic gene cluster was confirmed in A. niger, which revealed the involvement of a previously undescribed gene, pyrE, in its biosynthesis. UVC sensitivity assays enabled characterization of pyranonigrin A as a UV resistance agent in the ISS isolate.